- #1

Marth361

- 3

- 0

Hi I'm doing a project in math and seem to be stuck on one part.

I come to trying to solve this recursion equation given by...

f(x) = -f(x-1) + g(x) where g(x) is known.

Would anyone mind showing me how to go around solving for f(x)?

In this case i have g(x)=x[tex]^{2}[/tex] and f(0)=0 and f(1)=1

but will need to solve for any g(x) later on.

Thank You!

I come to trying to solve this recursion equation given by...

f(x) = -f(x-1) + g(x) where g(x) is known.

Would anyone mind showing me how to go around solving for f(x)?

In this case i have g(x)=x[tex]^{2}[/tex] and f(0)=0 and f(1)=1

but will need to solve for any g(x) later on.

Thank You!

Last edited: